2011
DOI: 10.4103/0019-5049.90608
|View full text |Cite
|
Sign up to set email alerts
|

Chirality and anaesthetic drugs: A review and an update

Abstract: Many molecules can exist as right-handed and left-handed forms that are non-superimposable mirror images of each other. They are known as enantiomers or substances of opposite shape. Such compounds are also said to be chiral (Greek chiros meaning ‘hand’). Such chiral molecules are of great relevance to anaesthetic theory and practice. This review summarizes the basic concepts, pharmacokinetic and pharmacodynamic aspects of chirality, and some specific examples of their application in anaesthesia, along with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 62 publications
0
24
1
Order By: Relevance
“…Within the classi cation of chiral medicines, racemates (74%) predominated with single enantiomer medicines (26%). These ndings contrast most of studies that indicate an increased number of single enantiomer drugs and only 25-40% of medicines are used as racemic medicines [15,32]. A review on chirality done in Japan [19] and in United Kingdom (UK) [33] reported the tendency of registration approval of medicines has been observed to be towards chiral switching or development of the pure enantiomer.…”
Section: Discussionmentioning
confidence: 86%
“…Within the classi cation of chiral medicines, racemates (74%) predominated with single enantiomer medicines (26%). These ndings contrast most of studies that indicate an increased number of single enantiomer drugs and only 25-40% of medicines are used as racemic medicines [15,32]. A review on chirality done in Japan [19] and in United Kingdom (UK) [33] reported the tendency of registration approval of medicines has been observed to be towards chiral switching or development of the pure enantiomer.…”
Section: Discussionmentioning
confidence: 86%
“…In clinical practice, barbital anesthetics are provided as a racemi mixture without specifying the enantiomeric ratio. For further safety in anesthetic development, enantiomeric ratio control is indispensable together with clarifying the action and side actions of individual enantiomers [1].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of chirality plays an important role in the life of animals and plants in addition to pharmaceutical, agrochemical and other chemical industries . Many compounds associated with living organisms including proteins, enzymes, carbohydrates, nucleosides, alkaloids, and hormones are chiral.…”
Section: Introductionmentioning
confidence: 99%